2022
DOI: 10.3390/ijerph19053023
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Disease Status on Loneliness of the Elderly: Evidence from Rural China

Abstract: At present, the dual pressure of rural labor outflow and population aging in China makes the problems of the rural elderly population increasingly prominent, and its health problem is particularly prominent. Based on the 2014 China elderly population health survey data (CLHLS), this paper finds that the physical health status of the rural elderly has a significant positive impact on their loneliness; that is, the rural elderly with poor health status are more likely to feel lonely. At the same time, the age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Intergenerational emotional support can provide motivation to the elderly to participate in social activities, which in turn relieves their loneliness and enhances their subjective well-being [ 45 , 46 ]. With emotional support from their children, elderly migrants become more confident in communicating with others in new environments [ 47 , 48 ]. Therefore, the children should provide emotional support to the elderly who migrated to new places [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intergenerational emotional support can provide motivation to the elderly to participate in social activities, which in turn relieves their loneliness and enhances their subjective well-being [ 45 , 46 ]. With emotional support from their children, elderly migrants become more confident in communicating with others in new environments [ 47 , 48 ]. Therefore, the children should provide emotional support to the elderly who migrated to new places [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intergenerational emotional support can enhance subjective well-being through serially reducing loneliness and increasing self-esteem. Migration can aggravate the loneliness of the elderly, especially when emotional support from their families lacks [ 48 , 54 ]. According to a sociometric theory, people with a feeling of isolation or interpersonal rejection tend to exhibit a lower self-esteem [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is a prognostic factor for worsened health and cognitive status in the elderly [22], which is already impaired by the sensory deficits common in old age, especially visual impairment [23]. on the other hand, elderly people with poor health status are also more likely to suffer from loneliness, and any episode of severe illness is likely to exacerbate this; chronic diseases do not have such a pronounced effect [24]. The sense of loneliness can also lead to a decrease in the quality of life of elderly people, especially those who live with three or more diseases [25].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of symptoms of end-stage diseases, Song et al [ 19 ]found that hypertension and diabetes did not affect the loneliness of older adults in normal times. However, as these chronic diseases progressed to end-stage symptoms, they elicited stronger loneliness.…”
Section: Loneliness At the End Of Lifementioning
confidence: 99%